Sistem Informasi Pengolahan Surat Masuk Dan Keluar Berbasis Website Pada SD Negeri 3 Sesetan Denpasar - Sugiartawan, Putu; Palus, Petrus; Suprihanto, Didit (Jurnal Sistem Informasi dan Komputer Terapan Indonesia (JSIKTI), 2021)
Mail management is a tangled thread that becomes the main problem in a company or organization. The information contained in the letter is an essential part of maintaining the confidentiality of data. Maintaining the integrity of the data becomes an essence that must be resolved in an organized manner so that incoming letters can be structured in a structured way and make it easier to search for these letters in the future. In general, the processing of incoming and outgoing mail is grouped and managed by similar grouping documents. The mail processing process still uses a number system or an agenda book, so document archiving is not optimal and less efficient in mail processing. To makes letters more organized, an information system is needed that can record and store the process of receiving letters. Using information systems directly can shorten searching for letters and storing notes in a more well-structured manner. The grouping of letters using the classification model of the decision tree algorithm can organize letters into specific groups. The set aims to speed up searching for correspondence information and the grouping to be more well structured. This study aims to build a mail processing information system. The system built can manage incoming and outgoing mail data. The research conducted in building this system is qualitative research by observing the research object.